2016
DOI: 10.1039/c5tb02579f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically controlled release of recombinant tissue plasminogen activator from chitosan nanocomposites for targeted thrombolysis

Abstract: Targeted delivery and triggered release of rtPA-encapsulated magnetic chitosan nanoparticles with the guidance of a magnet could be used for remote-controlled thrombolysis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…(e) The inhibition of free rtPA, PMNP-rtPA, and pPMNP-rtPA by plasminogen activator inhibitor-1 (PAI-1) in vitro by measuring the residual amidolytic activity of rtPA after incubating with PAI-I at 37 °C for different times. We further used thromboelastometry to determine blood clots lysis induced by rtPA by measuring the lysis index, which was shown to be dosage-dependent on free rtPA concentration used for the assay, to evaluate the thrombolytic effects [38]. As shown in Figure 3d, there is no significant difference in lysis index among free rtPA, PMN-rtPA and pPMNP rtPA irrespective of assay time (30, 45, 60 and 120 min) at the same rtPA drug dosage, which is in accordance with those from agar plate assays ( Figure 3c).…”
Section: Preparation Of Peptide and Rtpa Conjugated Plga Magnetic Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) The inhibition of free rtPA, PMNP-rtPA, and pPMNP-rtPA by plasminogen activator inhibitor-1 (PAI-1) in vitro by measuring the residual amidolytic activity of rtPA after incubating with PAI-I at 37 °C for different times. We further used thromboelastometry to determine blood clots lysis induced by rtPA by measuring the lysis index, which was shown to be dosage-dependent on free rtPA concentration used for the assay, to evaluate the thrombolytic effects [38]. As shown in Figure 3d, there is no significant difference in lysis index among free rtPA, PMN-rtPA and pPMNP rtPA irrespective of assay time (30, 45, 60 and 120 min) at the same rtPA drug dosage, which is in accordance with those from agar plate assays ( Figure 3c).…”
Section: Preparation Of Peptide and Rtpa Conjugated Plga Magnetic Nanmentioning
confidence: 99%
“…We further used thromboelastometry to determine blood clots lysis induced by rtPA by measuring the lysis index, which was shown to be dosage-dependent on free rtPA concentration used for the assay, to evaluate the thrombolytic effects [38]. As shown in Figure 3d, there is no significant difference in lysis index among free rtPA , PMN-rtPA and pPMNP rtPA irrespective of assay time (30, 45, 60 and 120 min.)…”
Section: Characterization Of Physico-chemical Propertiesmentioning
confidence: 99%
“…Lipid and/or PEGylated nanostructures encapsulating a thrombolytic drug were first reported and showed benefit from increasing the drug half-life [11][12][13][14]. More recently, this strategy was combined with active targeting approaches, mostly based on magnetic guidance [15][16][17][18][19]. Once accumulated on the thrombus, nanocarriers improve thrombolytic efficiency while reducing hemorrhagic complications, in preclinical models of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been further adapted by one research group that produced recombinant tissue plasminogen activator (rtPA) encapsulated magnetic chitosan nanoparticles. 82 They found that they could prevent the release of rtPA, a drug that induces thrombolysis, by applying a magnetic field to their nanoparticles in serum. Furthermore, they found that the removal of the magnetic field allowed for the release of the drug.…”
Section: Multimodal Imaging Of Atherosclerosis Using Iron Oxide Nanopmentioning
confidence: 99%